1999
DOI: 10.1124/mol.56.2.334
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic Effect of Buprenorphine in a Nociceptin/OFQ Receptor-Triggered Reporter Gene Assay

Abstract: The role of the opioid-like receptor 1 (ORL1) and its endogenous ligand, nociceptin/orphanin FQ (N/OFQ), in nociception, anxiety, and learning remains to be defined. To allow the rapid identification of agonists and antagonists, a reporter gene assay has been established in which the ORL1 receptor is functionally linked to the cyclic AMP-dependent expression of luciferase. N/OFQ and N/OFQ(1-13)NH(2) inhibited the forskolin-induced luciferase gene expression with IC(50) values of 0.81 +/- 0.5 and 0.87 +/- 0.16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 22 publications
1
62
1
Order By: Relevance
“…By preparing a number of compounds structurally related to NNC 63-0532 we observed that a naphthyl group in the 8-position was optimal for obtaining high a nity and selectivity for ORL1 (Watson et al, 1999). The a nity of NNC 63-0532 for ORL1 is about 10 fold lower as compared to nociceptin but almost similar to buprenorphine's ORL1 a nity (Wnendt et al, 1999). However, when compared to previously described nonpeptide agonists acting at ORL1 such as lofentanil and buprenorphine which have selectivity ratios (expressed as mopioid/ORL1 K i -ratios) of 0.001 and 0.06, respectively the similar ratio for NNC 63-0532 (*20) is much more favourable.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…By preparing a number of compounds structurally related to NNC 63-0532 we observed that a naphthyl group in the 8-position was optimal for obtaining high a nity and selectivity for ORL1 (Watson et al, 1999). The a nity of NNC 63-0532 for ORL1 is about 10 fold lower as compared to nociceptin but almost similar to buprenorphine's ORL1 a nity (Wnendt et al, 1999). However, when compared to previously described nonpeptide agonists acting at ORL1 such as lofentanil and buprenorphine which have selectivity ratios (expressed as mopioid/ORL1 K i -ratios) of 0.001 and 0.06, respectively the similar ratio for NNC 63-0532 (*20) is much more favourable.…”
Section: Discussionmentioning
confidence: 78%
“…Selective non-peptide ORL1 agonists and antagonists would therefore be highly advantageous in such studies. Very recently, a high a nity and selective ORL1 antagonist, (1-[(3R,4R)-1-cyclooctylmethyl-3-hydroxymethyl-4-piperidyl]-3-ethyl-1,3-dihydro-2H-benzimidazol-2-one) has been described (Kawamoto et al, 1999) but only a few non-peptide ORL1 agonists have been reported including lofentanil (K i =24 nM), etorphine (K i =530 nM) (Butour et al, 1997) and buprenorphine (IC 50 =8.4 nM) (Wnendt et al, 1999). Unfortunately, all of these compounds display a quite unfavourable selectivity ratio for ORL over other opioid receptors such as the m-opioid receptor (their respective K i 's for the m-opioid receptor are 0.023 nM, 0.18 nM and 0.51 nM (Maguire et al, 1992;Raynor et al, 1995)).…”
mentioning
confidence: 99%
“…Buprenorphine has recently been shown to interact with the ORL-1 receptor (Table 1) [2,26,31,53,105]. For example, we have shown that buprenorphine causes activation of the mitogenactivated protein kinase with similar efficacy but lower potency than OFQ/N in Chinese Hamster Ovary (CHO) cells expressing ORL-1 receptors [53].…”
Section: Introductionmentioning
confidence: 83%
“…The other possibility could be the slow dissociation rate of buprenorphine from the MOP (for reviews see Cowan, 2003;Lutfy and Cowan, 2004;Robinson, 2002;Tzschentke, 2002). A third explanation is that buprenorphine interacts with receptors other than the MOP (BlomsFunke et al, 2000;Hawkinson et al, 2000;Ide et al, 2004;Kajiwara et al, 1986;Lutfy et al, 2003;Negus et al, 1989Negus et al, , 2002Sadee et al, 1982;Wnendt et al, 1999; for review see Cowan, 2003;Lutfy and Cowan, 2004). The ability of buprenorphine to interact with the ORL-1 receptor (also known as NOP) is of a particular interest in this regard since orphanin FQ/ nociceptin, the endogenous ligand of the ORL-1 receptor (Meunier et al, 1995;Reinscheid et al, 1995), have been shown to block the analgesic (for review see Mogil and Pasternak, 2001) and rewarding (Ciccocioppo et al, 2000;Murphy et al, 1999) action of morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Although buprenorphine is described as a partial agonist at the MOP (Martin et al, 1976; for reviews see Cowan, 2003;Lutfy and Cowan, 2004;Ohlsen and Pilowsky, 2005;Robinson, 2002;Tzschentke, 2002), its mechanism of action is not fully understood For example, there is evidence showing its interaction with the kappa and delta opioid receptors as well as with the opioid receptor-like (ORL-1) receptor (Bloms-Funke et al, 2000;Hawkinson et al, 2000;Huang et al, 2001;Lutfy et al, 2003;Negus et al, 1989Negus et al, , 2002Sadee et al, 1982;Wnendt et al, 1999; for review see Lutfy and Cowan, 2004). Thus, buprenorphine represents an opioid with unique and complex pharmacology because it can simultaneously act as an agonist and/or antagonist at different classes of opioid receptors.…”
Section: Introductionmentioning
confidence: 99%